Positive electrode material and preparation method thereof, positive plate and battery

By mixing lithium iron phosphate with pore-forming agent, surfactant, silane coupling agent and carbon source, and heat treatment, a lithium iron phosphate positive electrode material with a carbon coated layer is solved, and the lithium iron phosphate material is significantly improved.

CN119852370APending Publication Date: 2025-04-18JIANGSU ZENIO NEW ENERGY BATTERY TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510076217.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The electronic conductivity and lithium ion diffusion rate of lithium iron phosphate cathode material are low, resulting in its actual specific capacity and poor circulation performance, limiting its large-scale application in the field of power batteries.

Method used

By mixing lithium iron phosphate, pore-forming agent, surfactant, silane coupling agent and carbon source, adjusting to an acidic environment and performing heating reaction, obtaining a precursor coated by carbon source, and heat treatment is performed under a protective gas atmosphere to form lithium iron phosphate with a carbon coated layer.

Benefits of technology

The electronic conductivity and ionic conductivity of the positive electrode material are improved, the uniformity and stability of the carbon cladding layer are enhanced, the interface impedance is reduced, and the capacity performance and cycle life of the positive electrode material are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852370A_ABST
    Figure CN119852370A_ABST
Patent Text Reader

Abstract

The embodiment of the invention relates to a preparation method of a positive electrode material, and the preparation method comprises the following steps: S1, dispersing lithium iron phosphate, a pore forming agent, a surfactant, a silane coupling agent and a carbon source in an alcohol solvent, adding a pH regulator, adjusting to an acidic environment, carrying out a heating reaction, and carrying out suction filtration, washing and drying to obtain a precursor coated with the carbon source; and S2, performing heat treatment on the precursor coated with the carbon source in a protective gas atmosphere to obtain lithium iron phosphate with a carbon coating layer. Therefore, the capacity performance and the cycle life of the finally prepared positive electrode material can be effectively improved and prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a positive electrode sheet and a battery. Background Art

[0002] Lithium iron phosphate, as a widely used positive electrode material, has the advantages of low price, high theoretical capacity, long cycle life and good structural thermal stability during lithium ion insertion and extraction.

[0003] However, in the crystal structure of lithium iron phosphate, FeO 6 The octahedron shares vertices. 4 Tetrahedral separation, no continuous FeO 6 The electrons can only be conducted through Fe-O-Fe in the octahedral network, which results in a low electronic conductivity of lithium iron phosphate, which is only 10 -9 S / cm; at the same time in LiO 6 Octahedron and FeO 6 PO between octahedrons 4 Tetrahedral confinement of Li + The mobile space of Li + The diffusion rate is low, only 1.8*10 -16 cm 2 / s~2.2*10 -14 cm 2 / s. Therefore, the actual specific capacity of lithium iron phosphate positive electrode materials is not high and the cycle performance is poor, which limits the large-scale application of lithium iron phosphate materials in the field of power batteries.

[0004] At present, researchers have improved the capacity and cycle performance of lithium iron phosphate cathode materials to a certain extent through research on nano-sizing and doping modification of lithium iron phosphate materials. However, in order to better meet the needs of actual applications, the capacity and cycle performance of lithium iron phosphate cathode materials still need to be further improved. Summary of the invention

[0005] In view of this, the embodiments of the present application provide a positive electrode material and a preparation method thereof, a positive electrode sheet and a battery to solve at least one problem existing in the background technology.

[0006] In a first aspect, an embodiment of the present application provides a method for preparing a positive electrode material, the method comprising the following steps:

[0007] S1: dispersing lithium iron phosphate, a pore-forming agent, a surfactant, a silane coupling agent and a carbon source in an alcohol solvent, adding a pH adjuster, adjusting to an acidic environment, heating to react, filtering, washing and drying to obtain a carbon source-coated precursor;

[0008] S2: Under a protective gas atmosphere, heat-treating the carbon source-coated precursor to obtain lithium iron phosphate with a carbon coating layer.

[0009] In conjunction with the first aspect of the present application, in an optional implementation manner, step S1 satisfies at least one of the following features:

[0010] (1) The molar ratio of the lithium iron phosphate, the pore-forming agent, the surfactant, the silane coupling agent and the carbon source is K1:K2:K3:K4:K5, wherein 90≤K1≤94.5, 0<K2≤3, 0<K3≤4, 0<K4≤3, 1≤K5≤5;

[0011] (2) The pore-forming agent includes at least one of zinc acetate, zinc nitrate, zinc chloride, zinc sulfide, and zinc sulfate;

[0012] (3) The surfactant includes at least one of a cationic surfactant, an anionic surfactant, and a nonionic surfactant;

[0013] (4) The chemical formula of the silane coupling agent is RSiX 3 , wherein R comprises at least one of an oxy group, a thiol group, a vinyl group, an epoxy group, an amide group, and an aminopropyl group, and X comprises a halogen or a hydrolyzable alkoxy group;

[0014] (5) The carbon source includes at least one of sucrose, glucose, starch, cellulose, graphene, and carbon nanotubes;

[0015] (6) The alcohol solvent includes at least one of methanol, ethanol, isopropanol, and ethylene glycol;

[0016] (7) The pH adjuster includes at least one of carbonic acid, citric acid, malic acid, and sodium bisulfite;

[0017] (8) The acidic environment is an acidic environment with a pH of 2 to 5.5;

[0018] (9) The drying temperature is 45°C to 85°C.

[0019] In conjunction with the first aspect of the present application, in an optional embodiment, the heating reaction in step S1 satisfies at least one of the following characteristics:

[0020] (1) The temperature of the heating reaction is 45° C. to 90° C.;

[0021] (2) The heating reaction time is 1 h to 4 h;

[0022] (3) The heating reaction is carried out under reflux stirring conditions.

[0023] In conjunction with the first aspect of the present application, in an optional embodiment, the washing process in step S1 includes:

[0024] The product obtained after the heating reaction is washed until the pH value of the supernatant is 6.5-7.5.

[0025] In conjunction with the first aspect of the present application, in an optional implementation manner, step S2 satisfies at least one of the following features:

[0026] (1) The heating rate of the heat treatment is 1°C / min to 50°C / min;

[0027] (2) The temperature of the heat treatment is 700° C. to 1000° C.;

[0028] (3) The heat treatment holding time is 1h to 4h;

[0029] (4) The protective gas includes an inert gas.

[0030] In conjunction with the first aspect of the present application, in an optional implementation manner, the step of preparing lithium iron phosphate in step S1 includes:

[0031] Dispersing a lithium source and phosphoric acid in a solvent, adding an iron source and a reducing agent, and stirring evenly to obtain a mixed solution;

[0032] The mixed solution is subjected to heating treatment, cooled, centrifuged, washed and dried to obtain the lithium iron phosphate.

[0033] In conjunction with the first aspect of the present application, in an optional embodiment, the preparation step of the lithium iron phosphate satisfies at least one of the following characteristics:

[0034] (1) The lithium source includes lithium carbonate and / or lithium hydroxide;

[0035] (2) The iron source includes at least one of ferrous sulfate, ferrous acetate, ferric nitrate, ferric phosphate, and ferric oxide;

[0036] (3) The reducing agent includes at least one of ascorbic acid, hydrazine hydrate, and hydroxylamine hydrochloride;

[0037] (4) The temperature of the heating treatment is 100° C. to 200° C.;

[0038] (5) The heating treatment time is 5h to 12h;

[0039] (6) The centrifugal speed is 8000 rpm to 11000 rpm;

[0040] (7) The centrifugation time is 5 min to 15 min;

[0041] (8) The drying temperature is 45°C to 85°C.

[0042] In a second aspect, an embodiment of the present application provides a positive electrode material, which is prepared using the method for preparing the positive electrode material described in any one of the first aspects.

[0043] In a third aspect, an embodiment of the present application provides a positive electrode sheet, which includes the positive electrode material described in the second aspect.

[0044] In a fourth aspect, an embodiment of the present application provides a battery, comprising the positive electrode sheet described in the third aspect.

[0045] Compared with the prior art, the embodiments of the present application have the following beneficial effects:

[0046] The positive electrode material and its preparation method, positive electrode sheet and battery provided in the embodiments of the present application, in the preparation method of the positive electrode material, lithium iron phosphate, a pore-forming agent, a surfactant, a silane coupling agent and a carbon source are mixed, adjusted to an acidic environment, and then reacted to obtain a carbon source-coated precursor, wherein the surfactant can improve the dispersibility of the carbon source, and the silane coupling agent can modify the surface of the lithium iron phosphate to make the surface of the lithium iron phosphate organic, and the synergistic effect of the two can promote the carbon source to form a uniform, complete and stable coating on the surface of the lithium iron phosphate, so that the lithium iron phosphate is modified by a one-step reaction to obtain a carbon source-coated precursor, which is simple to operate, low in cost, and convenient for mass production; since the carbon source A uniform, complete and stable coating is formed on the surface of lithium iron phosphate, and then the carbon source coated precursor is heat treated to improve the uniformity and stability of the carbon coating formed on the surface of lithium iron phosphate, thereby improving the electronic conductivity of the positive electrode material, reducing the corrosion of the electrolyte to the positive electrode material and the dissolution of the transition metal, thereby maintaining the structural integrity of the positive electrode material and reducing the interface impedance. In addition, during the heat treatment process, the pore-forming agent in the carbon source coated precursor decomposes and evaporates due to heat, which can form pores in the carbon coating layer, promote the transmission of lithium ions, thereby improving the ionic conductivity of the positive electrode material. Therefore, the capacity performance and cycle life of the final positive electrode material can be effectively improved.

[0047] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0049] Figure 1A schematic diagram of a process for preparing a positive electrode material provided in an embodiment of the present application;

[0050] Figure 2 The cycle performance test curves of batteries made of the positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0051] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is described in detail by combining the accompanying drawings and listing specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually based on conventional experimental conditions. The reagents and raw materials used in the present invention are commercially available unless otherwise specified.

[0052] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.

[0053] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "a", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. The terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.

[0054] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.

[0055] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.

[0056] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.

[0057] This application embodiment provides a method for preparing a positive electrode material. Figure 1 The method for preparing the positive electrode material provided in the embodiment of the present application comprises the following steps:

[0058] S1: dispersing lithium iron phosphate, a pore-forming agent, a surfactant, a silane coupling agent and a carbon source in an alcohol solvent, adding a pH adjuster, adjusting to an acidic environment, heating to react, filtering, washing and drying to obtain a carbon source-coated precursor;

[0059] S2: Under a protective gas atmosphere, heat-treating the carbon source-coated precursor to obtain lithium iron phosphate with a carbon coating layer.

[0060] In an embodiment of the present application, first, lithium iron phosphate, a pore-forming agent, a surfactant, a silane coupling agent and a carbon source are mixed, adjusted to an acidic environment, and then reacted to obtain a carbon source-coated precursor, wherein the surfactant can improve the dispersibility of the carbon source, and the silane coupling agent can modify the surface of the lithium iron phosphate. For example, the hydrolysis of the groups in the silane coupling agent will form silanols, and the silanols can react with the groups on the surface of the lithium iron phosphate to form covalent bonds. At the same time, the silanols of each molecule in the silane coupling agent can be interconnected through association and polymerization reactions to form a network structure film covering the surface of the lithium iron phosphate, so that the surface of the lithium iron phosphate is organic. The synergistic effect of the two can promote the carbon source to form a uniform, complete and stable coating on the surface of the lithium iron phosphate. In this way, the lithium iron phosphate is modified by a one-step reaction to obtain a carbon source-coated precursor. The process is simple, low in cost and convenient for mass production; next, the carbon source-coated precursor is heat-treated to obtain lithium iron phosphate with a carbon coating layer. Since the carbon source forms a uniform and complete coating on the surface of the lithium iron phosphate, the uniformity and stability of the carbon coating layer formed on the surface of the lithium iron phosphate can be improved, thereby improving the electronic conductivity of the positive electrode material, reducing the corrosion of the electrolyte on the positive electrode material and the dissolution of the transition metal, thereby maintaining the structural integrity of the positive electrode material and reducing the interface impedance. In addition, during the heat treatment process, the pore-forming agent in the carbon source-coated precursor is decomposed and evaporated by heat, and pores can be formed in the carbon coating layer, which promotes the transmission of lithium ions, thereby improving the ionic conductivity of the positive electrode material. Therefore, the capacity performance and cycle life of the positive electrode material finally obtained can be effectively improved.

[0061] In some embodiments, the molar ratio of lithium iron phosphate, pore-forming agent, surfactant, silane coupling agent and carbon source in step S1 can be K1: K2: K3: K4: K5, wherein 90≤K1≤94.5, 0<K2≤3, 0<K3≤4, 0<K4≤3, 1≤K5≤5. For example, the molar ratio of lithium iron phosphate, pore-forming agent, surfactant, silane coupling agent and carbon source can be 90: 0.1: 0.1: 0.1: 1, 92: 1: 1: 1: 2, 93: 2: 2: 2: 4, 94.5: 3: 4: 4: 5 or any other ratio within the above molar ratio range.

[0062] In the embodiment of the present application, controlling the molar ratio of lithium iron phosphate, pore-forming agent, surfactant, silane coupling agent and carbon source within the above range can ensure that the carbon source coats the lithium iron phosphate more evenly and completely, thereby better improving the uniformity and stability of the subsequently obtained carbon coating layer, and further improving the performance of the finally obtained positive electrode material.

[0063] There is no particular restriction on the types of the pore-forming agent, surfactant and silane coupling agent in the above step S1, and they can be selected according to actual needs.

[0064] The pore-forming agent in step S1 is mixed in the carbon source coating layer, and can be decomposed and evaporated by heat during the subsequent heat treatment process to form pores in the carbon coating layer. For example, the pore-forming agent may include at least one of zinc acetate, zinc nitrate, zinc chloride, zinc sulfide, and zinc sulfate.

[0065] Taking zinc oxide as an example, during the heat treatment process, zinc oxide will be reduced by carbon to form zinc, and zinc vapor will evaporate and leave the carbon coating, leaving pores (also called nanopores) in the carbon coating. For example, at high temperature (e.g., around 900°C), the reaction formula of zinc oxide and carbon is: 2ZnO+C=2Zn↑+CO 2 ↑.

[0066] The surfactant in step S1 may include, for example, at least one of a cationic surfactant, an anionic surfactant, and a nonionic surfactant. These surfactants can improve the dispersibility of the mixed material, reduce or avoid the occurrence of carbon source agglomeration, and thus promote a more uniform coating of the carbon source on the surface of lithium iron phosphate.

[0067] Specifically, cationic surfactants may include, for example, cetyltrimethylammonium bromide (CTAB), anionic surfactants may include, for example, sodium dodecyl sulfate (SDS), and nonionic surfactants may include, for example, sorbitan fatty acid esters (Span series), Tween series, and the like.

[0068] The chemical formula of the silane coupling agent in step S1 can be RSiX3 , wherein R represents an active functional group having affinity or reaction ability with the polymer molecule, specifically, R may include at least one of oxy, thiol, vinyl, epoxy, amide, and aminopropyl, and X includes halogen or hydrolyzable alkoxy, specifically, X may include halogen, alkoxy, or acyloxy, etc.

[0069] Exemplarily, the silane coupling agent may include vinyl triethoxysilane (A151), vinyl trimethoxysilane (A171), vinyl tri(β-methoxyethoxy)silane (A172), 3-aminopropyl trimethoxysilane, methyl tri(methoxy)silane, 3-propyleneoxypropyl trimethoxysilane, 1H,1H,2H,2H-perfluorooctyl trimethoxysilane, and the like.

[0070] In the embodiment of the present application, when the silane coupling agent is coupled, the X group is first hydrolyzed to form silanol, and then reacts with the hydroxyl group on the surface of the lithium iron phosphate (inorganic powder particles) to form a hydrogen bond and condense into a SiO-M covalent bond, where M represents the surface of the lithium iron phosphate. At the same time, the silanol of each silane molecule forms a network structure film covering the surface of the lithium iron phosphate through mutual association polymerization reaction, so that the surface of the lithium iron phosphate is organic, which can improve the integrity and stability of the carbon source coating on the surface of the lithium iron phosphate. In addition, silane coupling agents usually contain heteroatoms (specifically, F, S, N, etc.). For example, perfluorosilane (FAS-17) contains heteroatom F, γ-mercaptopropyltrimethoxysilane contains heteroatom S, and γ-cyanoethyltrimethoxysilane contains heteroatom N. During the subsequent heat treatment process, the heteroatoms can enter the carbon coating layer for doping. Since the heteroatoms have a large electronegativity, the conductivity of the positive electrode material can be further improved. At the same time, certain defects can be caused in the carbon coating layer, thereby improving the transmission efficiency of lithium ions, and then the electrochemical performance of the positive electrode material can be improved.

[0071] In the embodiments of the present application, there are many choices of silane coupling agents and surfactants, and those skilled in the art can make choices based on actual needs to adjust the formula of the coating layer to obtain a positive electrode material with comprehensive performance that can meet different battery requirements.

[0072] The carbon source in step S1 refers to a compound for providing carbon. For example, the carbon source may include at least one of sucrose, glucose, starch, cellulose, graphene, and carbon nanotubes.

[0073] The alcohol solvent in step S1 may include, for example, at least one of methanol, ethanol, isopropanol, and ethylene glycol.

[0074] The pH adjuster in step S1 may include, for example, at least one of carbonic acid, citric acid, malic acid, and sodium bisulfite.

[0075] Under the regulation of the pH regulator, the acidic environment in step S1 can be an acidic environment with a pH of 2 to 5.5. Specifically, the pH can be, for example, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, or any value between any two of the above numerical ranges. This can promote the reaction in step S1 to proceed more fully, thereby further improving the uniformity, integrity and stability of the carbon source coating, and obtaining a higher quality carbon source coated precursor.

[0076] Further, the acidic environment in step S1 may be an acidic environment with a pH of 3.5 to 5.5. Further, the acidic environment in step S1 may be an acidic environment with a pH of 4 to 5. In a specific embodiment, the acidic environment in step S1 may be an acidic environment with a pH of 4.5.

[0077] In some embodiments, the temperature of the heating reaction in step S1 can be 45°C to 90°C, for example, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or any value between any two of the above ranges. This can promote the full progress of the reaction, thereby further improving the uniformity, integrity and stability of the carbon source coating, and obtaining a higher quality carbon source coated precursor.

[0078] In some embodiments, the heating reaction time in step S1 can be 1 h to 4 h, for example, 1 h, 2 h, 3 h, 4 h or any value between any two of the above ranges. This can ensure that the reaction is more thorough, thereby further improving the quality of the carbon source-coated precursor.

[0079] In some specific embodiments, step S1 may include, for example: first, dispersing lithium iron phosphate, a pore-forming agent, a surfactant, a silane coupling agent and a carbon source in an alcohol solvent, adding a pH adjuster, adjusting to an acidic environment, and stirring to make the components evenly dispersed (for example, stirring for 15 minutes to 60 minutes); next, heating the reaction under reflux stirring conditions, and then filtering, washing and drying to obtain a carbon source-coated precursor.

[0080] In the embodiment of the present application, the heating reaction is carried out under reflux stirring conditions, which can enable a more complete reaction on the surface of the lithium iron phosphate, thereby improving the uniformity of the silane coupling agent, carbon source, and pore-forming agent coating on the surface of the lithium iron phosphate, and further improving the quality of the obtained carbon source-coated precursor.

[0081] In some specific embodiments, the washing treatment in step S1 may include: washing the product obtained after the heating reaction until the pH value of the supernatant is 6.5 to 7.5, for example, 6.5, 7, 7.5 or any value between any two of the above numerical ranges. This helps to remove the pH regulator, residual silane coupling agent, surfactant and pore-forming agent in the product, thereby improving the uniformity and stability of the carbon coating layer in the subsequent heat treatment, enhancing the connectivity between lithium iron phosphate and the carbon coating layer, making the two difficult to separate, and reducing the content of impurities in the finally formed carbon coating layer, thereby further improving the performance of the positive electrode material.

[0082] In the actual preparation process, for example, ethanol and water may be used to wash the product alternately for multiple times until the pH value of the supernatant reaches the required value. In a specific embodiment, the washing treatment in step S1 may include: washing the product obtained after the heating reaction until the pH value of the supernatant is 7. That is, washing the product until the supernatant is neutral, so that the pH regulator, residual silane coupling agent, surfactant and pore-forming agent in the product can be better removed.

[0083] In some embodiments, the drying temperature in step S1 may be 45° C. to 85° C., for example, 45° C., 55° C., 65° C., 75° C., 85° C., or any value between any two of the above ranges. In this way, the product obtained by the heating reaction can be effectively dried. Specifically, for example, the drying process can be performed in an oven.

[0084] In some embodiments, the heating rate of the heat treatment in step S2 can be 1°C / min to 50°C / min, for example, 1°C / min, 10°C / min, 20°C / min, 30°C / min, 40°C / min, 50°C / min or any value between any two of the above numerical ranges.

[0085] In the embodiment of the present application, the heating rate is controlled within the above range, so that the material can be heated more evenly, and the influence of excessive heating rate on the microstructure of the carbon coating layer can be avoided, as well as the problem of excessive defects in the carbon coating layer caused by rapid heating, which is beneficial to improving the performance of the prepared positive electrode material.

[0086] In some embodiments, the temperature of the heat treatment in step S2 may be 700° C. to 1000° C., for example, 700° C., 800° C., 900° C., 1000° C. or any value between any two of the above ranges.

[0087] In the embodiment of the present application, the temperature of the heat treatment is controlled within the above range, so that the carbon source and silane coupling agent coated on the surface of the lithium iron phosphate can be fully carbonized, which is beneficial to improving the quality of the carbon coating layer, thereby helping to further improve the performance of the prepared positive electrode material.

[0088] In some embodiments, the holding time of the heat treatment in step S2 can be 1 h to 4 h, for example, 1 h, 2 h, 3 h, 4 h or any value between any two of the above ranges.

[0089] In the embodiment of the present application, controlling the holding time of the heat treatment within the above range can further enhance the effect of the heat treatment, and can promote the degree to which the heteroatoms contained in the silane coupling agent enter the carbon layer, thereby enhancing the effect of heteroatoms doping the carbon coating layer, thereby facilitating further enhancing the performance of the obtained positive electrode material.

[0090] In the actual preparation process, the carbon source coated precursor can be placed in a tube furnace, and sintered (heat treated) under the protection of a protective gas. After the sintering treatment is completed, the temperature is naturally lowered to obtain lithium iron phosphate with a carbon coating layer. Exemplarily, the protective gas may include an inert gas, specifically, for example, at least one of nitrogen, argon, and helium.

[0091] It can be understood that the above-mentioned heat treatment temperature, holding time and heating rate range can be arbitrarily combined, for example, any two or all three can be combined, so as to achieve a better heat treatment effect and further improve the performance of the prepared positive electrode material.

[0092] In the embodiment of the present application, the coating of lithium iron phosphate does not change the crystal structure of the material itself, the prepared carbon coating layer has a uniform thickness, and can coat the lithium iron phosphate relatively completely, which can greatly enhance the conductivity of the lithium iron phosphate material, reduce the corrosion of the lithium iron phosphate material by the electrolyte byproducts, and reduce the probability of structural distortion caused by the dissolution of transition metals in the lithium iron phosphate, thereby reducing the interface impedance. Therefore, the selection range of the positive electrode material for the electrolyte can be expanded.

[0093] In the present application, the lithium iron phosphate used in step S1 may also be referred to as pure phase lithium iron phosphate. The preparation steps of the lithium iron phosphate in step S1 may include: dispersing a lithium source and phosphoric acid in a solvent, adding an iron source and a reducing agent, and stirring to obtain a mixed solution; heating the mixed solution, cooling it, centrifuging, washing, and drying it to obtain lithium iron phosphate.

[0094] Exemplarily, the lithium source may include lithium carbonate and / or lithium hydroxide. The iron source may include at least one of ferrous sulfate, ferrous acetate, ferric nitrate, ferric phosphate, and ferric oxide. The reducing agent may reduce trivalent iron ions to divalent iron ions, increase the reaction activity, and thereby ensure the formation of active particles during the heat treatment process. Specifically, the reducing agent may include at least one of ascorbic acid, hydrazine hydrate, and hydroxylamine hydrochloride.

[0095] In the above-mentioned preparation step of lithium iron phosphate, the temperature of the heating treatment can be 100°C to 200°C, for example, 100°C, 150°C, 200°C or any value between any two of the above-mentioned numerical ranges; further, the time of the heating treatment can be 5h to 12h, for example, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or any value between any two of the above-mentioned numerical ranges. Controlling the temperature and time of the heating treatment within the above-mentioned range is conducive to improving the quality of the obtained lithium iron phosphate.

[0096] In the above-mentioned preparation steps of lithium iron phosphate, the centrifugal speed can be 8000rpm~11000rpm, for example, it can be 8000rpm, 9000rpm, 10000rpm, 11000rpm or any value between any two numerical ranges mentioned above. The centrifugal time can be 5min~15min, for example, it can be 5min, 10min, 15min or any value between any two numerical ranges mentioned above. The temperature of the drying treatment can be 45℃~85℃, for example, it can be 45℃, 55℃, 65℃, 75℃, 85℃ or any value between any two numerical ranges mentioned above. Controlling the speed and time of the centrifugal treatment and the temperature of the drying treatment within the above-mentioned range is conducive to improving the quality of the obtained lithium iron phosphate.

[0097] In the actual preparation process, the preparation steps of lithium iron phosphate may include: dispersing 0.5 mol to 3 mol of lithium source and 0.5 mol to 2 mol of phosphoric acid in 1 L to 5 L of alcohol solvent (such as ethylene glycol), stirring at room temperature for 15 min to 60 min, then adding 0.1 mol to 1 mol of iron source and 0.1 mol to 0.5 mol of reducing agent (such as ascorbic acid), stirring at room temperature for 15 min to 60 min; next, transferring the mixture to a reactor and heating it at 100°C to 200°C for 5 h to 12 h; after cooling to room temperature, centrifuging the mixture at a speed of 8000 rpm to 11000 rpm for 5 min to 15 min, then washing it alternately with ethanol and water for multiple times (for example, 3 times), and finally drying the precipitate in a 45°C to 85°C oven to obtain lithium iron phosphate.

[0098] The embodiment of the present application also provides a positive electrode material, which is prepared by the preparation method of the positive electrode material described in any of the above embodiments.

[0099] The embodiment of the present application also provides a positive electrode sheet, which includes the positive electrode material described in the above embodiment.

[0100] It should be understood that the beneficial effects of the positive electrode material obtained by the method for preparing the positive electrode material described in any of the above embodiments are all applicable to the positive electrode sheet.

[0101] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer may include the positive electrode material described in the above embodiments.

[0102] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer may be provided on any one or both of the two facing surfaces of the positive electrode current collector.

[0103] An embodiment of the present application further provides a battery, which includes the positive electrode sheet described in the above embodiment.

[0104] It should be understood that the beneficial effects of the positive electrode sheet in the above embodiments are all applicable to the battery.

[0105] In some embodiments, the battery may be a secondary battery, and the secondary battery may be a lithium-ion secondary battery. Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions, lithium ions, are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0106] The technical solution of the present application is further described below in combination with a plurality of embodiments and comparative examples.

[0107] Example 1

[0108] The preparation of the positive electrode material in this embodiment includes the following steps:

[0109] Step S101: 1.5 mol of lithium hydroxide (lithium source) and 0.5 mol of phosphoric acid are dispersed in 4 L of ethylene glycol (solvent), and stirred at room temperature for 30 min. Then, 0.5 mol of ferrous sulfate heptahydrate (iron source) and 0.2 mol of ascorbic acid (reducing agent) are added, and stirred at room temperature for 30 min. Next, the mixture is transferred to a reactor and heated at 150° C. for 10 h. After cooling to room temperature, the mixture is centrifuged at a speed of 10000 rpm for 10 min, and then washed alternately with ethanol and water for 3 times. Finally, the precipitate is placed in an oven at 60° C. to dry to obtain lithium iron phosphate.

[0110] Step S102: The lithium iron phosphate, zinc chloride (pore former), CTAB (surfactant), A171 (silane coupling agent) and glucose (carbon source) prepared in step S101 are dispersed in ethanol in a molar ratio of 92.5:2:1.5:1.5:2.5, and the pH is adjusted to 4.5 with acetic acid. Stir for 30 minutes, then reflux and stir at 60°C for 2 hours, then filter, and wash alternately with ethanol and water several times until the pH of the supernatant is close to 7. Finally, the material is placed in an oven at 60°C to dry to obtain a surface-coated lithium iron phosphate material (carbon source-coated precursor).

[0111] Step S103: Place the surface-coated lithium iron phosphate material obtained in step S102 in a tubular furnace, and under the protection of inert gas nitrogen, heat it to 700°C at a heating rate of 5°C / min, keep it warm for 4 hours, and then cool it naturally to obtain lithium iron phosphate (positive electrode material) with a carbon coating layer.

[0112] Example 2

[0113] The preparation method of the positive electrode material in this embodiment is basically the same as that in embodiment 1, except that:

[0114] In step S101, the lithium source is lithium carbonate, the amount of lithium carbonate added is 1.5 mol, the iron source is ferrous acetate, the amount of ferrous acetate added is 1 mol;

[0115] In step S102, the pore-forming agent is zinc acetate, the surfactant is SDS, the silane coupling agent is A151, the carbon source is sucrose, and the molar ratio of lithium iron phosphate, zinc acetate, SDS, A151 and sucrose is 93.5:1.5:1.5:1.5:2.

[0116] Example 3

[0117] The preparation method of the positive electrode material in this embodiment is basically the same as that in embodiment 1, except that:

[0118] In step S101, the iron source is iron oxide, and the amount of iron oxide added is 0.6 mol;

[0119] In step S102, the pore-forming agent is zinc nitrate, the surfactant is Span80, the silane coupling agent is A172, the carbon source is starch, and the molar ratio of lithium iron phosphate, zinc nitrate, Span80, A172 and starch is 91.5:2.5:2:1.5:2.5.

[0120] Example 4

[0121] The preparation method of the positive electrode material in this embodiment is basically the same as that in embodiment 1, except that:

[0122] In step S103, the heating rate is 10°C / min and the holding time is 2h.

[0123] Comparative Example 1

[0124] The preparation method of the positive electrode material in this comparative example is basically the same as that in Example 1, except that:

[0125] In step S102 , the pore-forming agent zinc chloride is not added, and the molar ratio of lithium iron phosphate, CTAB, A171 and glucose is 93.5:2.5:2:2.

[0126] Comparative Example 2

[0127] The preparation method of the positive electrode material in this comparative example is basically the same as that in Example 1, except that:

[0128] In step S102 , the surfactant CTAB is not added, and the molar ratio of lithium iron phosphate, zinc chloride, A171 and glucose is 92.5:3:2.5:2.

[0129] Comparative Example 3

[0130] The preparation method of the positive electrode material in this comparative example is basically the same as that in Example 1, except that:

[0131] In step S102 , silane coupling agent A171 is not added, and the molar ratio of lithium iron phosphate, zinc chloride, CTAB and glucose is 93:2.5:2.5:2.

[0132] The positive electrode materials prepared in the above embodiments and comparative examples were prepared into batteries and electrochemical performance tests were performed, wherein the preparation method of the battery comprises the following steps:

[0133] (1) Preparation of positive electrode sheet: First, the positive electrode materials, conductive agents and binders prepared in the above-mentioned embodiments and comparative examples were mixed uniformly in a mass ratio of 96.5:1.5:2, added into a solvent N-methylpyrrolidone (NMP), and stirred uniformly to form a stable positive electrode slurry; Next, the positive electrode slurry was applied to the positive electrode current collector by transfer coating, and a positive electrode roll was obtained after drying, and a positive electrode sheet was obtained after rolling, wherein the coating weight of the positive electrode slurry was 0.4 g / 1540.25 mm 2 , the coating thickness is 0.216mm.

[0134] (2) Preparation of negative electrode sheet: First, the negative electrode active material, conductive agent and binder were mixed in a mass ratio of 95.5:2.5:2, added into deionized water, and stirred to form a stable negative electrode slurry; Next, the negative electrode slurry was coated onto the negative electrode current collector by transfer coating, and the negative electrode roll was obtained after drying, and the negative electrode sheet was obtained after rolling, wherein the coating weight of the negative electrode slurry was 0.187 g / 1540.25 mm2 , the coating thickness is 0.16mm.

[0135] (3) Preparation of electrolyte: LiPF 6 It is dissolved in a mixed solvent of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in a volume ratio of 1.5:1:0.5 to form an electrolyte with a concentration of 1.2 mol / L.

[0136] (4) Assembling batteries: The separator uses a polypropylene base film with a thickness of 9 μm, and the two surfaces in the thickness direction of the base film are coated with polyvinylidene fluoride (PVDF) with a thickness of 3 μm and aluminum oxide with a thickness of 3 μm in sequence. The positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, and the battery cell is assembled by winding. The electrolyte is injected into the dry battery cell, and a lithium-ion soft-pack battery is obtained after formation and capacity separation.

[0137] It should be noted that, for each embodiment and each comparative example, the conductive agent and binder used in preparing the positive electrode sheet are the same, and the negative electrode active material, conductive agent and binder used in preparing the negative electrode sheet are the same.

[0138] The discharge capacity and cycle performance of the above battery are tested. The specific test steps are as follows:

[0139] Step (1): In a 25°C incubator, charge the battery to 3.65V at a constant current of 0.33C, charge the battery to a current cutoff of 0.05C at a constant voltage of 3.65V, let it stand for 30 minutes, then discharge the battery to 2.5V at a constant current of 0.33C, let it stand for 30 minutes, and cycle the battery for three weeks. The capacity in the last week is the actual discharge capacity C0 of the battery.

[0140] Step (2): In a 25°C oven, charge at a constant current of 1C to 3.65V, charge at a constant voltage of 3.65V to a current cutoff of 0.05C, let stand for 30 minutes, discharge at a constant current of 1C to 2.5V, let stand for 30 minutes, repeat the 1C cycle, divide the discharge capacity of each cycle by the discharge capacity (C0) of the first cycle to obtain the cycle capacity retention rate, stop the cycle when the cycle capacity retention rate reaches 80%, that is, the discharge capacity is 0.8*C0, and record the number of cycles. It should be noted that in the above cycle test process, the discharge capacity is retested every 200 cycles according to the test method in the above step (1) to correct the cycle current size and maintain the cycle at a rate of 1C.

[0141] The discharge capacity of the batteries corresponding to each embodiment and each comparative example and the number of cycles at which the capacity retention rate is 80% are shown in Table 1.

[0142] Table 1

[0143] Discharge capacity / Ah Number of cycles at which the capacity retention rate is 80% / cycle Example 1 3.68 1092 Example 2 3.66 893 Example 3 3.59 834 Example 4 3.33 745 Comparative Example 1 2.85 369 Comparative Example 2 3.16 502 Comparative Example 3 3.31 542

[0144] Figure 2 The cycle performance test curves of the batteries made of the positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 are shown. Figure 2 It can be seen that when the battery cycle capacity retention rate is 80%, the number of cycles of the batteries made of the positive electrode materials prepared in Examples 1 to 4 is significantly higher than the number of cycles of the batteries made of the positive electrode materials prepared in Comparative Examples 1 to 3. For specific data, please refer to the results in Table 1. From the data in Table 1, it can be seen that the discharge capacity and the number of cycles with a capacity retention rate of 80% of the batteries corresponding to all the embodiments are higher than the discharge capacity and the number of cycles with a capacity retention rate of 80% of the batteries corresponding to all the comparative examples. This shows that in the present application, by mixing lithium iron phosphate, a pore-forming agent, a surfactant, a silane coupling agent and a carbon source, a one-step reaction is performed to obtain a carbon source-coated precursor. Since the surfactant can improve the dispersibility of the carbon source, the silane coupling agent can modify the surface of the lithium iron phosphate, so that the surface of the lithium iron phosphate is organic, and the synergistic effect of the two can promote the carbon source to form a uniform, complete and stable coating on the surface of the lithium iron phosphate. Not only is the operation simple, but the cost is low. By heat treating the carbon source-coated precursor, the uniformity and stability of the carbon coating layer formed on the surface of the lithium iron phosphate can be improved, thereby improving the electronic conductivity of the positive electrode material, reducing the corrosion of the electrolyte to the positive electrode material and the dissolution of the transition metal, thereby maintaining the structural integrity of the positive electrode material and reducing the interface impedance. In addition, during the heat treatment process, the pore-forming agent in the carbon source-coated precursor is thermally decomposed and evaporated, and pores can be formed in the carbon coating layer, which promotes the transmission of lithium ions, thereby improving the ionic conductivity of the positive electrode material. Therefore, the capacity performance and cycle life of the positive electrode material finally obtained can be effectively improved.

[0145] From the data comparison of Example 4 and Example 1 in Table 1, it can be seen that since the heating rate of the heat treatment in Example 4 is higher than that in Example 1, the rapid heating is likely to affect the microstructure of the carbon coating layer, which may lead to more defects in the carbon coating layer, thereby reducing the capacity performance and cycle life of the positive electrode material. Therefore, appropriately reducing the heating rate of the heat treatment is conducive to further improving the comprehensive performance of the positive electrode material.

[0146] From the data comparison between Comparative Example 1 and Example 1 in Table 1, it can be seen that since no pore-forming agent is added in the preparation method of the positive electrode material in Comparative Example 1, certain pores cannot be formed in the carbon coating layer formed after heat treatment. Therefore, it is difficult to improve the ionic conductivity of the positive electrode material, thereby significantly reducing the capacity performance and cycle life of the prepared positive electrode material.

[0147] From the data comparison between Comparative Example 2 and Example 1 in Table 1, it can be seen that since no surfactant is added in the preparation method of the positive electrode material in Comparative Example 2, the dispersibility of the mixed material is poor, and the carbon source is easily agglomerated on the surface of the lithium iron phosphate, resulting in uneven coating, thereby significantly reducing the capacity performance and cycle life of the prepared positive electrode material.

[0148] From the data comparison between Comparative Example 3 and Example 1 in Table 1, it can be seen that since no silane coupling agent is added in the preparation method of the positive electrode material in Comparative Example 3, the surface of the lithium iron phosphate cannot be effectively modified. Therefore, it is difficult to improve the integrity and stability of the carbon source coating on the surface of the lithium iron phosphate, and further difficult to improve the uniformity and stability of the carbon coating layer obtained after heat treatment, thereby significantly reducing the capacity performance and cycle life of the prepared positive electrode material.

[0149] It can be seen from the above that in the preparation method of the positive electrode material of the present application, the pore-forming agent, the surfactant and the silane coupling agent are indispensable, otherwise it is difficult to effectively improve the capacity performance and cycle life of the positive electrode material.

[0150] In the present application, the mixed material is evenly dispersed by a surfactant, and the surface of the lithium iron phosphate is modified by a silane coupling agent, so that a high-quality carbon coating layer combining a silane coupling agent and a carbon source is constructed on the surface of the lithium iron phosphate material particles, and then pores are formed in the carbon coating layer by a pore-forming agent, which can effectively improve the capacity performance and cycle life of the positive electrode material, thereby effectively improving the performance of the battery.

[0151] It should be noted that the positive electrode material embodiments, positive electrode material preparation method embodiments, positive electrode sheet embodiments and battery embodiments provided in the present application belong to the same concept; the technical features in the technical solutions recorded in each embodiment can be combined arbitrarily without conflict.

[0152] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.

Claims

1. A method for preparing a positive electrode material, characterized in that: The method comprises the following steps: S1: dispersing lithium iron phosphate, a pore-forming agent, a surfactant, a silane coupling agent and a carbon source in an alcohol solvent, adding a pH adjuster, adjusting to an acidic environment, heating to react, filtering, washing and drying to obtain a carbon source-coated precursor; S2: Under a protective gas atmosphere, heat-treating the carbon source-coated precursor to obtain lithium iron phosphate with a carbon coating layer.

2. The method for preparing the positive electrode material according to claim 1, characterized in that: Step S1 satisfies at least one of the following characteristics: (1) The molar ratio of the lithium iron phosphate, the pore-forming agent, the surfactant, the silane coupling agent and the carbon source is K1:K2:K3:K4:K5, wherein 90≤K1≤94.5, 0<K2≤3, 0<K3≤4, 0<K4≤3, 1≤K5≤5; (2) The pore-forming agent includes at least one of zinc acetate, zinc nitrate, zinc chloride, zinc sulfide, and zinc sulfate; (3) The surfactant includes at least one of a cationic surfactant, an anionic surfactant, and a nonionic surfactant; (4) The chemical formula of the silane coupling agent is RSiX3, wherein R includes at least one of an oxy group, a thiol group, a vinyl group, an epoxy group, an amide group, and an aminopropyl group, and X includes a halogen or a hydrolyzable alkoxy group; (5) The carbon source includes at least one of sucrose, glucose, starch, cellulose, graphene, and carbon nanotubes; (6) The alcohol solvent includes at least one of methanol, ethanol, isopropanol, and ethylene glycol; (7) The pH adjuster includes at least one of carbonic acid, citric acid, malic acid, and sodium bisulfite; (8) The acidic environment is an acidic environment with a pH of 2 to 5.5; (9) The drying temperature is 45°C to 85°C.

3. The method for preparing the positive electrode material according to claim 1, characterized in that: The heating reaction in step S1 satisfies at least one of the following characteristics: (1) The temperature of the heating reaction is 45° C. to 90° C.; (2) The heating reaction time is 1 h to 4 h; (3) The heating reaction is carried out under reflux stirring conditions.

4. The method for preparing the positive electrode material according to claim 1, characterized in that: The washing process in step S1 includes: The product obtained after the heating reaction is washed until the pH value of the supernatant is 6.5-7.

5.

5. The method for preparing the positive electrode material according to claim 1, characterized in that: Step S2 satisfies at least one of the following characteristics: (1) The heating rate of the heat treatment is 1°C / min to 50°C / min; (2) The temperature of the heat treatment is 700° C. to 1000° C.; (3) The heat treatment holding time is 1h to 4h; (4) The protective gas includes an inert gas.

6. The method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: The steps for preparing lithium iron phosphate in step S1 include: Dispersing a lithium source and phosphoric acid in a solvent, adding an iron source and a reducing agent, and stirring evenly to obtain a mixed solution; The mixed solution is subjected to heating treatment, cooled, centrifuged, washed and dried to obtain the lithium iron phosphate.

7. The method for preparing the positive electrode material according to claim 6, characterized in that: The preparation step of the lithium iron phosphate satisfies at least one of the following characteristics: (1) The lithium source includes lithium carbonate and / or lithium hydroxide; (2) The iron source includes at least one of ferrous sulfate, ferrous acetate, ferric nitrate, ferric phosphate, and ferric oxide; (3) The reducing agent includes at least one of ascorbic acid, hydrazine hydrate, and hydroxylamine hydrochloride; (4) The temperature of the heating treatment is 100° C. to 200° C.; (5) The heating treatment time is 5h to 12h; (6) The centrifugal speed is 8000 rpm to 11000 rpm; (7) The centrifugation time is 5 min to 15 min; (8) The temperature of the drying process is 45°C to 85°C.

8. A positive electrode material, characterized in that The cathode material is prepared by the method for preparing the cathode material according to any one of claims 1 to 7.

9. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode material according to claim 8.

10. A battery, characterized in that: Including the positive electrode sheet as claimed in claim 9.

Citation Information

Patent Citations

  • Lithium iron phosphate / carbon composite material with surface modified by coupling agent and preparation method thereof

    CN101964412A

  • Method for preparing lithium iron phosphate / carbon composite material of lithium ion battery

    CN102013477A

  • Coupling agent-modified composite lithium iron phosphate positive electrode material and preparation method thereof

    CN103545484A

  • Modified silicon monoxide / carbon nanotube composite negative electrode material and preparation method thereof

    CN112678807A

  • Lithium iron phosphate / carbon composite material, preparation method thereof, positive pole piece and lithium ion battery

    CN113745481A